Phytocystatin CsinCPI-2 Reduces Osteoclastogenesis and Alveolar Bone Loss - Da Ponte Leguizamón, N. [UNESP]; de Molon, R. S. [UNESP]; Coletto-Nunes, G. [UNESP]; Nogueira, A. V.B.; Rocha, S. V.; Neo-Justino, D. M.; Soares-Costa, A.; Cerri, P. S. [UNESP]; Lerner, U. H.; Souza, P. P.C.; Cirelli, J. A. [UNESP] (SAGE Publications, 2022)
Periodontal disease (PD) is a polymicrobial chronic inflammatory condition of the supporting tissues around the teeth, leading to the destruction of surrounding connective tissue. During the progression of PD, osteoclasts play a crucial role in the resorption of alveolar bone that eventually leads to the loss of teeth if the PD is left untreated. Therefore, the development of antiresorptive therapies targeting bone-resorbing cells will significantly benefit the treatment of PD. Here, we demonstrate the inhibitory effect of CsinCPI-2, a novel cysteine peptidase inhibitor from the orange tree, on periodontitis-induced inflammation, alveolar bone loss, and osteoclast differentiation. Using the ligature-induced periodontitis model in mice, we show that treatment with CsinCPI-2 (0.8 µg/g of body weight) significantly reduced inflammatory cell infiltrate in the connective tissue and prevented the loss of alveolar bone mass (BV/TV) caused by PD, effects associated with diminished numbers of TRAP-positive multinucleated cells. Furthermore, CsinCPI-2 significantly downregulated the numbers of inflammatory cells expressing CD3, CD45, MAC387, and IL-1β. In vitro, CsinCPI-2 inhibited RANKL-induced TRAP+ multinucleated osteoclast formation in mouse bone marrow macrophage cultures in a concentration-dependent manner. This effect was not due to cytotoxicity, as demonstrated by the MTT assay. CsinCPI-2 inhibited RANKL-induced mRNA expression of Acp5, Calcr, and Ctsk, as well as the RANKL-induced upregulation of Nfatc1, a crucial transcription factor for osteoclast differentiation. Based on our findings, CsinCPI-2 prevents bone loss induced by PD by controlling the inflammatory process and acting directly on osteoclastogenesis, suggesting an interesting potential for CsinCPI-2 in the strategy for PD treatment.
Keywords: bone resorption; cystatins; inflammation; osteoclasts; periodontal diseases; periodontitis